RHEUMATOID ARTHRITIS: ETIOLOGY, SYMPTOMS, DIAGNOSIS, TREATMENT - Muhammadiyeva S. M.; Boltaboyeva M. Sh.; Butayev A. I. (Web of Journals Publishing, 2026)
This article discusses the etiology, pathogenesis, clinical manifestations, diagnostic approaches and modern treatment strategies of rheumatoid arthritis based on the most recent data.
Keywords: Rheumatoid arthritis; pathogenesis; genetic susceptibility; HLA-DRB1; anti-CCP antibodies; immune dysregulation; DMARDs; biological therapy.